Group decision and negotiation : theory, empirical evidence, and application : 16th International Conference, GDN 2016, Bellingham, WA, USA, June 20-24, 2016, revised selected papers /: theory, empirical evidence, and application : 16th International Conference, GDN 2016, Bellingham, WA, USA, June 20-24, 2016, revised selected papers. (2017) - Unknown
No abstract available